Do gender regimes matter? Gender differences in involvement in anti-austerity protests - a comparison of Spain, Sweden and the United Kingdom. (3rd May 2020) - Roth, Silke; Saunders, Clare
ABSTRACT: Responses to the Great Recession are varied across welfare states and gendered in their consequences. Combining gender, social policy and social movement scholarship, this paper investigates how the differential policy responses to the Financial Crisis in three European countries shaped gender-differences in anti-austerity demonstrations. We compare the involvement and characteristics of women and men in anti-austerity protests using data collected at street demonstrations (2010–2012). We conduct cross-national multi-level analysis of demonstrators from countries representing different gender regimes (Spain, Sweden and the United Kingdom). Our results show that gender regimes have a significant impact on women's and men's involvement in anti-austerity protests. We thus make an important contribution to research on gender differences in participation in anti-austerity demonstrations post-Great Recession. Our comparison of women's and men's participation in anti-austerity street demonstrations suggests that at the country or regime level resources matter more than grievances, but that grievances matter at the individual level. This innovative paper links scholarship on gender regimes with research on protest participation. Resources and experiences of grievances are shaped by gender regimes which provide access to decision-making and social support. We reveal novel insights into the connection between gender regimes and demonstration participation.